PEMILIHAN SUPPLIER PENGADAAN PERANGKAT SISTEM GEMPA BUMI DENGAN METODE ANALYTICAL HIERARCHY PROCESS (AHP) PADA PT.LEN INDUSTRI - Hari Fadlisyah; Moch Fadli Fathoroni H; Dea Zahra Azizah; Muchammad Fauzi (Jurnal Taguchi : Jurnal Ilmiah Teknik dan Manajemen Industri, 2022)
In this growing age, more and more companies and new businesses are emerging. This results in increasingly fierce competition between business competition in goods or services. Every company must have support for businesses that must be sought to generate maximum profit by adding costs. This can be realized by companies with the right supplier selection. Suppliers who cannot cause problems can cause significant losses to the company. PT Len Industri is currently engaged in the electronics industry.. LEN also continues to actively support the country by providing products in the fields of defense, transportation and ICT (Information & Communication Technology). So far the company still chooses suppliers in the usual way. This study studies to study how the application of basic AHP suppliers at PT. Len Industri. This research is a way to select suppliers of earthquake system equipment procurement at this time by the company, what are the weaknesses and strengths of supplier selection implemented by the company, what problems occur in the production process related to the selection of suppliers of earthquake system equipment earth, what criteria are used in the selection of suppliers